Fashion and film : moving images and consumer behavior - Bug, Peter (Springer, 2020)
This book aims to explore various aspects of the use of moving images in fashion retail and fashion apparel companies in-store or online. The use of moving images is growing in numbers and in relevance for consumers. Films can be used in various forms by fashion businesses in traditional media like cinema or TV and in modern forms like in social media or moving images in high street stores. The book provides a data-oriented analysis of the state-of-the-art with certain future outlooks. Additional areas of covering fashion in moving images, such as 'fashion company identity films or 'fashion and music videos are covered in order to get a more complete analysis from a consumer influenced perspective.- Resumé vydavatel
Keywords: spotřebitelské chování; móda; odívání; televize; film; maloobchod; internetové sociální sítě; consumer behavior; fashion; clothing; television; retail trade; Internet social networks; elektronické knihy; sborníky; electronic books; papers of several authors